Todo empezó en el "53”: historia oral de un distrito liberacionista - Fernández González, Alvaro (1992)
In the period alter 1953, the district of Concepción de Tres Ríos has a undergone a deep transformations: from a typical coffee producing town to a suburb where urban works –mostly immigrants from others parts of the country- reside. This article discusses forms of communal politics and partisan politics in the Liberacionista district.